(untitled) (Journal of Geography and Environmental Management, 2018)
The Russian-Kazakh border zone is a region that has a common historical, geographical, ethnic and economic space. The course on the achievement of the conjugacy of the development of the Eurasian Economic Union and the formation of the Economic belt of the Silk Road creates prerequisites for crossborder integration of the regions of the Russian Federation and the Republic of Kazakhstan. All this gives grounds for a more detailed consideration of the Russian-Kazakhstan integration processes. The study of the current state of the population in the borderland makes it possible to assess the prospects of demographic processes on both sides of the state border and the geopolitical consequences of the dynamics of population change. Article is intended to provide a demographic profile of the population in the north-western Kazakh-Russian border area for 1991-2016. To determine the specifics of demographic processes in regional border areas, a statistical method of investigation was used. As a result of the study, it was revealed that in the Russian border zone the population exceeds the population in the Kazakh border area by 5 times. However, natural growth is negative in the Russian border zone, while in Kazakhstan it is positive. The demographic situation in the studied regions of the Russian-Kazakh borderland reflects the contradictions of the transition period.